Classical archaeology of ancient Greece and Rome - Hale, John R.; Teaching Company (Chantilly, VA : Teaching Co., 2006)
Classical archaeology, the excavation and analysis of ancient Greek and Roman sites, has been one of the leading branches of archaeology, pioneering its basic methods and major innovations. In these 36 half-hour lectures, Dr. John R. Hale of the University of Louisville guides the listener through 18th-century excavations at Herculaneum and Pompeii, tours many important archaeological sites or discoveries, from the Bronze Age to late antiquity, and takes a thematic approach in exploring what archaeology has contributed to knowledge of ancient diet, entertainment, engineering, slavery, religion, the role of women, and other topics.
Fakulti Teknologi Kreatif dan Warisan.
Lecturer: john R. hale
Keywords: Archaeology -- Greece; Archaeology -- Italy; Classical antiquities; Speeches, addresses, etc